Signaling pathway intervention in premature ovarian failure - Bai, Xuefeng; Wang, Shaowei (Frontiers in Medicine, 2022)
Premature ovarian failure (POF) is a multifactorial disease that refers to the occurrence of secondary amenorrhea, estrogen decrease, and gonadotropin increase in women under the age of 40. The prevalence of POF is increasing year by year, and the existing instances can be categorized as primary or secondary cases. This disease has adverse effects on both the physiology and psychology of women. Hormone replacement therapy is the recommended treatment for POF, and a multidisciplinary strategy is required to enhance the quality of life of patients. According to recent studies, the primary mechanism of POF is the depletion of ovarian reserve function as a result of increased primordial follicular activation or primordial follicular insufficiency. Therefore, understanding the processes of primordial follicle activation and associated pathways and exploring effective interventions are important for the treatment of POF